Influences of the circadian clock on neuronal susceptibility to excitotoxicity - Tischkau, Shelley A.; Karmarkar, Sumedha W. (Frontiers in Physiology, 2013)
Stroke is the third leading cause of death and the primary cause of morbidity in the United States, thus posing an enormous burden on the healthcare system. The factors that determine the risk of an individual towards precipitation of an ischemic event possess a strong circadian component as does the ischemic event itself. This predictability provided a window of opportunity towards the development of chronopharmaceuticals which provided much better clinical outcomes. Experiments from our lab showed for the first time that neuronal susceptibility to ischemic events follows a circadian pattern; hippocampal neurons being most susceptible to an ischemic insult occurring during peak activity in a rodent model of global cerebral ischemia. We also demonstrated that the SCN2.2 cells (like their in vivo counterpart) are resistant to excitotoxicity by glutamate and that this was dependent on activation of ERK signaling. We are currently working on elucidating the complete neuroprotective pathway that provides a barricade against glutamate toxicity in the SCN2.2 cells. Our future experiments will be engaged in hijacking the neuroprotective mechanism in the SCN2.2 cells and applying it to glutamate-susceptible entities in an effort to prevent their death in the presence of excitotoxicity. Despite the advancement in chronopharmaceuticals, optimal clinical outcome with minimal adverse events are difficult to come by at an affordable price. Superior treatment options require a better understanding of molecular mechanisms that define the disease, including the role of the circadian clock.